TEACHING PRACTICE AND PLAYFULNESS: PEDAGOGICAL REFLECTIONS IN EARLY CHILDHOOD EDUCATION - de Oliveira, Isabel Pereira; Santos, Iracy de Sousa (Seven Editora, 2025)
This article reflects on teaching practice and playfulness focusing on the pedagogical actions used for the socialization and learning of children in an early childhood education center. The theme under study aims to highlight the importance of play in an early childhood education center, specifically in the first and second periods of this level of education. Our interest in the theme consists of questioning how the pedagogical practices developed by teachers in this phase of education have contributed to the significant learning of children. Thus, our objective was to analyze how teachers use playfulness in their teaching practices as pedagogical tools. The pedagogical practice through playfulness is a dynamic action in constant movement, requiring planning to ensure the realization of the proposed intentionalities. This study is qualitative in nature, and the subjects of the research were 10 teachers from an Early Childhood Education Center in Lagoa Grande do Maranhão. Open questionnaires were applied and the results revealed that the pedagogical practice through playfulness is indispensable to enhance the teaching work and allow the integral development of the child in a pleasurable way. DOI: https://doi.org/10.56238/sevened2024.037-132